ANALISIS FRAMING PASCA PENUTUPAN LOKALISASI DOLLY SURABAYA PADA TERBITAN JAWAPOS.COM DAN KOMPASIANA.COM - Prakoso, Bintang Ferditama; Rochim, Achludin Ibnu; Soenarjanto, Bagus (Universitas 17 Agustus 1945 Surabaya, 2017)
Framing analysis in this study is used to find out how the reality (events, actors, groups andso forth) is constructed by the media. In what ways and techniques are the events emphasized andhighlighted. Whether in the news there are parts that are omitted, escaped or even hidden in the news.All of these elements are not only part of the technical journalism, but indicate how events areinterpreted and displayed. This study aims to find out how online media Java post and kompasianaframe news about post closing localization dolly surabaya. Subjects in this study were Java onlinemedium post on May 15, 2014 and kompasiana on June 26, 2014 closing dolly Surabaya localization.The research method used in this research is qualitative with technical framing analysis. The unit ofanalysis used in this study is the reference unit. The results of the research on framing analysis thereis a difference in the presentation of news between Java online media post and kompasiana. In termsof framing news (news).Keywords : Analysis of Framing, online media, online journalist